Effects of pH control by acid addition at the aqueous processing of cathodes for lithium ion batteries. (10th September 2019) - Bauer, Werner; Çetinel, Fatih A.; Müller, Marcus; Kaufmann, Ulrike
Abstract: The replacement of organic solvent-based electrode manufacturing by a water-based process offers the chance for a significant reduction of the manufacturing costs. However, the interaction of cathode materials with water changes their storage properties and causes massive problems for electrode manufacturing and cell properties. Due to a Li + /H + exchange reaction, the pH of the aqueous slurry is increased so that a corrosive attack of the aluminum foil takes place. The reduction of the pH value by the addition of an acid is a practical measure to prevent corrosion, but has also negative effects on slurry rheology, or electrode conductivity and adhesion. These consequences are shown in an exemplary way for the addition of acetic acid. As especially the adhesion strength is influenced, this effect is investigated in detail for various acids. Best electrode properties are not found in the stable region of the aluminum foil, but at a higher pH of 9–10. Acetic acid treated cells show high capacities at their begin-of-life, but undergo stronger degradation than samples without acid addition. Highlights: Acetic acid addition has significant impact on slurry and electrode behavior. Acetic and other acids can strongly decrease adhesion strength. pH reduction to the stability range of alumina impairs cell properties. Highest cell capacities are obtained at moderate reduction to pH 9-10. Acetic acid addition accelerates degeneration of the cells.